THE INFLUENCE OF PRICE AND SERVICE QUALITY OF BRAND IMAGE AND ITS IMPACT ON CUSTOMER SATISFACTION GOJEK (STUDENTS STUDY ON A STATE UNIVERSITY OF JAKARTA) - Rizan, Mohammad; Yulianti, Dahliana; Rahmi, Rahmi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2015)
The purpose of the research are to: test empirically influence of price to brand image on customer satisfaction Gojek, test empirically influence of service quality to brand image on customer satisfaction Gojek, test empirically influence of price on customer satisfaction Gojek, test empirically influence of service quality on customer satisfaction Gojek, test empirically influence of brand image on customer satisfaction Gojek. This study used confirmatory factor analysis. The research was conducted in State University of Jakarta and used purposive sampling techniques, while the data collecting technique used questionaire, SPSS and SEM LISREL for data processing. The result shows a significant influence of price and service quality for brand image and its impact on customer satisfaction. Keywords: price, service quality, brand image, customer satisfaction